Pelatihan Penggunaan Media Konkrit Berbasis Etnomatematika dalam Pembelajaran Matematika pada Guru Sekolah Dasar - Fredy Fredy; Lay Riwu; Ratna Purwanty (LPPM Universitas Flores, 2022)
One of the reasons why mathematics is still a scourge for elementary school students in the delivery of mathematics material that seems formal and the lack of involvement of interesting and contextual learning media. It needs the right approach and media to present formal mathematics material so that students are able to understand the material and its benefits in real-life contexts. One of them is to use local culture and wisdom as a concrete medium. The purpose of this PKM program is to improve the knowledge and skills of SD YPPK St. Elementary School teachers. Tarsisius Biankuk through training in the use of ethnomathematical-based concrete media in learning mathematics. The implementation method is through training with the stages of preliminary study, implementation, and evaluation. The results of the service show that the teacher can explain some of the culture and local wisdom that can be developed as learning media such as miniature bevak, areca nut, fishing gear for hunting and catching fish, musical instruments tifa, and darts. In addition, the teacher is also able to demonstrate ethnomathematical-based concrete media well. The PKM lecturer team continues to monitor and assist partner schools until the implementation of mathematics learning by applying ethnomathematical-based concrete media in real classes.